Robust interface on ENR-50/TiO2 nanohybrid material based sol-gel technique: Insights into synthesis, characterization and applications in optical - Omar, S. Dahham (Elsevier, 2020)
Link to publisher's homepage at https://www.journals.elsevier.com/arabian-journal-of-chemistry/